Conserved MicroRNA miR-8/miR-200 and Its Target USH/FOG2 Control Growth by Regulating PI3K. - Hyun, S.; Lee, J.H.; Jin, H.; Nam, J.; Namkoong, B.; Lee, G.; Chung, J.; Kim, V.N. (Cell, 2009)
How body size is determined is a long-standing question in biology, yet its regulatory mechanisms remain largely unknown. Here, we find that a conserved microRNA miR-8 and its target, USH, regulate body size in Drosophila. miR-8 null flies are smaller in size and defective in insulin signaling in fat body that is the fly counterpart of liver and adipose tissue. Fat body-specific expression and clonal analyses reveal that miR-8 activates PI3K, thereby promoting fat cell growth cell-autonomously and enhancing organismal growth non-cell-autonomously. Comparative analyses identify USH and its human homolog, FOG2, as the targets of fly miR-8 and human miR-200, respectively. USH/FOG2 inhibits PI3K activity, suppressing cell growth in both flies and humans. FOG2 directly binds to p85alpha, the regulatory subunit of PI3K, and interferes with the formation of a PI3K complex. Our study identifies two novel regulators of insulin signaling, miR-8/miR-200 and USH/FOG2, and suggests their roles in adolescent growth, aging, and cancer.